2019
DOI: 10.2514/1.b37133
|View full text |Cite
|
Sign up to set email alerts
|

Background Pressure Effects on Ion Velocity Distributions in an SPT-100 Hall Thruster

Abstract: Increased background pressure in vacuum chamber test facilities as compared to on-orbit operation has been shown to influence the operation of electric propulsion devices such as Hall thrusters. This study aims to elucidate the impact of pressure on the ionization and acceleration mechanisms in a stationary plasma thruster, model SPT-100 Hall thruster, using time-averaged and time-resolved laser-induced fluorescence velocimetry. The results are compared for the thruster operating at an applied 300 V (∼4.25 A),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…This result indicates that on the centerline ions are on average only accelerated in the z-direction over a long distance. The observation of significant ion acceleration from z = -6 mm to z = 70 mm in a cylindrical thruster plasma is remarkable because ion acceleration in conventional annular Hall thruster plasmas usually occurs only within 10 -20 mm from the thruster exit plane [1,[18][19][20]. is the ion mass, 𝑣 𝑧 and 𝑣 𝑟 are the axial and radial ion velocities, and 𝑓 𝑧 (𝑣 𝑧 ) is the axial ion velocity distribution function.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that on the centerline ions are on average only accelerated in the z-direction over a long distance. The observation of significant ion acceleration from z = -6 mm to z = 70 mm in a cylindrical thruster plasma is remarkable because ion acceleration in conventional annular Hall thruster plasmas usually occurs only within 10 -20 mm from the thruster exit plane [1,[18][19][20]. is the ion mass, 𝑣 𝑧 and 𝑣 𝑟 are the axial and radial ion velocities, and 𝑓 𝑧 (𝑣 𝑧 ) is the axial ion velocity distribution function.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive literature describes the effects of the background pressure on Hall Effect Thrusters testing re-vealing an influence on the performance, discharge channel physics and plume characteristics [20][21][22] . In particular, relevant to the results presented in this article, a recent study 23 has analysed the effect of the background pressure in the range 1.7 -8 × 10 −5 Torr on xenon ion velocity distribution functions in a SPT-100 thruster plume characterised through laser-induced fluorescence velocimetry. The analysis shows the background pressure influences the ionization and acceleration zones, with an observed upstream shift of the axial ion acceleration front when the pressure is increased; nevertheless, the ultimate ion velocity after acceleration appears unaffected.…”
Section: Methodsmentioning
confidence: 99%
“…The background pressure effects were investigated for 1.35-kW SPT-100, and it was reported that the backpressure of 6.7×10 −3 Pa caused a non-negligible performance change such as 4% increase in thrust, because a fraction of the background particles worked as propellant [12]. In addition, it was reported that the acceleration zone moved upstream by a few millimeters owing to the backpressure [13]. In this experiment, it was expected that these background pressure effects would increase the measured 𝑖 g .…”
Section: Methodsmentioning
confidence: 99%